2014
DOI: 10.1186/1743-0003-11-168
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive control interfaces for intention detection in active movement-assistive devices

Abstract: Active movement-assistive devices aim to increase the quality of life for patients with neuromusculoskeletal disorders. This technology requires interaction between the user and the device through a control interface that detects the user’s movement intention. Researchers have explored a wide variety of invasive and non-invasive control interfaces. To summarize the wide spectrum of strategies, this paper presents a comprehensive review focused on non-invasive control interfaces used to operate active movement-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 171 publications
(198 reference statements)
0
98
0
Order By: Relevance
“…Pilot trials showed that this measurement-based method was able to accurately estimate gravity and joint stiffness forces along the range of motion of the elbow. A video showing the compensation force measurement can be found in [249] as additional file 4. Figure 29 shows the control diagram of the physiological (i.e.…”
Section: Signal Processingmentioning
confidence: 99%
See 4 more Smart Citations
“…Pilot trials showed that this measurement-based method was able to accurately estimate gravity and joint stiffness forces along the range of motion of the elbow. A video showing the compensation force measurement can be found in [249] as additional file 4. Figure 29 shows the control diagram of the physiological (i.e.…”
Section: Signal Processingmentioning
confidence: 99%
“…The target angles located near the limits of the ROM were placed, within the ROM, 5 degrees from the limits in order to prevent collisions with the mechanical end-stops placed at the limits of the ROM. A video of one of the participants performing the discrete position-tracking task using the force-based control interface can be found in [249] as additional file 5.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 3 more Smart Citations